RELATIONSHIP OF SOCIAL SUPPORT WITH SELF ADJUSTMENT OF PENSION PERIOD IN TELKOM'S RETIREMENT UNIT (P2TEL) - Patricia Lunanta, Lita; Auliana,; M, Safitri; Sherlita, Erly (International Journal of Psychosocial Rehabilitation, 2020)
Retirement is a change that occurs in an employee who initially worked to become unemployed, or a change that includes losing a position, making a pension will feel no longer have self-respect by the environment, feel not getting attention, and care. This will show reactions such as being unable to control excessive emotions, being unrealistic, and unable to overcome feelings of frustration. The purpose of this study is to look at the relationship between social support and adjustment in retirement. A total of 100 research samples were collected from the Telkom Pensioners Association (P2TEL). The social support scale refers to the Sarafino theory with 27 items and reliability (α) 0.903 and the adjustment scale of the Scheneiders theory with 38 items and reliability (α) 0.876. The results showed a significant positive relationship (sig 0. 000 and r 0.410) between social support and the adjustment of P2TEL retirees. Based on the value of r 2 = 0.168 shows that social support influenced adjustment to 16.8%. Pensioners who have high social support (57%) and low social support (43%). P2TEL retirees who have a bad adjustment more (52%) compared to a good adjustment (48%). There is no relationship of conformity of retirees at P2TEL with people who are contacted by retirees when they have a problem.